The Role of Rho GTPases in VEGF Signaling in Cancer Cells - Nada El Baba; Mohammad Farran; Elie Abi Khalil; Leila Jaafar; Isabelle Fakhoury; Mirvat El-Sibai (Analytical Cellular Pathology)
Vascular endothelial growth factors (VEGFs) consist of five molecules (VEGFA through D as well as placental growth factor) which are crucial for regulating key cellular and tissue functions. The role of VEGF and its intracellular signaling and downstream molecular pathways have been thoroughly studied. Activation of VEGF signal transduction can be initiated by the molecules’ binding to two classes of transmembrane receptors: (1) the VEGF tyrosine kinase receptors (VEGF receptors 1 through 3) and (2) the neuropilins (NRP1 and 2). The involvement of Rho GTPases in modulating VEGFA signaling in both cancer cells and endothelial cells has also been well established. Additionally, different isoforms of Rho GTPases, namely, RhoA, RhoC, and RhoG, have been shown to regulate VEGF expression as well as blood vessel formation. This review article will explore how Rho GTPases modulate VEGF signaling and the consequences of such interaction on cancer progression.